Studi Sifat Kekerasan Material Pegas Daun Untuk Alat Perkakas Tangan Melalui Proses Penyepuhan Dengan Variasi Waktu Penahanan - Tuny, Semuel M. J. S; Waas, Victor D.; Battianan, Dominggus (Industrial Engineering Study Program, Pattimura University, 2025)
A study was conducted to investigate the effect of variation in holding time during the hardening process on the hardness of leaf spring steel. Used leaf spring steel is widely utilized as raw material for the manufacturing of hand tools by blacksmiths through hardening processes. Hardening is a heat treatment method aimed at enhancing the hardness of a material. The hardening process involves heating the material to a specific temperature (austenitizing temperature), holding it for a certain period, and then rapidly cooling it. This study aims to investigate the effect of variations in austenitizing holding time, specifically 30 seconds, 40 seconds, 45 seconds, 50 seconds, and 60 seconds, on the hardness value of leaf spring steel. The leaf spring steel material is subjected to heat treatment at an austenitizing temperature of 900°C, followed by quenching in oil. Hardness testing is performed using the Hardness Rockwell B (HRB) method. The results of the study indicate that hardening can enhance the hardness properties of leaf spring steel; however, as the holding time increases, the hardness level tends to decrease. The highest average hardness value was recorded at a holding time of 45 seconds, with a hardness value of 121 HRB.